Hydrophobic nanofiber and method for producing same
Patent Information
- Application Number
- JP2021001182
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-07
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-01-07
AI Technical Summary
【0011】 本発明によれば、疎水性ナノファイバー及びその製造方法を提供することができる。
Smart Images

Figure 0007640069000009 
Figure 0007640069000010 
Figure 0007640069000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a hydrophobic nanofiber and a method for producing the same. [Background technology]
[0002] Nanofibers are fibrous materials with an average diameter of about 1 to 100 nm and a length 100 times or more the diameter, and are classified into synthetic polymer nanofibers, natural polymer nanofibers, and carbon nanofibers depending on the raw material. Natural polymer nanofibers are obtained by using naturally occurring polysaccharides, and therefore have the advantage of effective use of biomass and safety.
[0003] On the other hand, fillers are being added to resins to improve their properties. When using fibrous materials as fillers to be added to resins, the fibrous materials must be hydrophobic and highly dispersible so that they can be kneaded into the resin. However, no natural polymer nanofibers with such properties have been known to date.
[0004] As a natural polymer nanofiber, cellulose nanofibers made from cellulose composed of β-1,4-glucan are known. Cellulose nanofibers are themselves hydrophilic and have the property of agglomerating in water. As a cellulose nanofiber with excellent dispersibility, chemically modified cellulose nanofibers (TEMPO oxidized cellulose nanofibers) are available, but they are also hydrophilic and have poor dispersibility in hydrophobic environments such as organic solvents. Patent Document 1 describes a resin composition containing a cellulose ester and a fluorene compound, but does not describe the formation of nanofibers.
[0005] The present inventors have previously applied various chemical modifications to paramylon, a storage polysaccharide produced by Euglena, and investigated its usefulness as biomass. Paramylon is a β-1,3-glucan having a structure in which glucose is linked by β-1,3 bonds. Patent Document 2 proposes nanofibers in which the 6-hydroxyl group of the glucose residue of β-1,3-glucan is acylated with a cyclic dicarboxylic acid. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-86254 A [Patent Document 2] JP 2014-37657 A Summary of the Invention [Problem to be solved by the invention]
[0007] The β-1,3-glucan nanofibers proposed in Patent Document 2 have improved cohesive strength between nanofibers due to intermolecular interactions between the acyl groups of the nanofiber molecules, and can form a film or the like without containing an additional adhesive component. In addition, the β-1,3-glucan nanofibers proposed in Patent Document 2 can be said to be hydrophilic nanofibers because they have anionic functional groups.
[0008] The present inventors have conducted extensive research into nanofibers that can be dispersed without aggregation in hydrophobic environments such as resins, organic solvents, etc. In the course of this research, they discovered that a gel-like nanofiber aggregate containing acylated β-1,3-glucan or a solid nanofiber aggregate obtained by drying the gel can be defibrated into individual nanofibers by immersing the aggregate in a specific organic solvent, which led to the completion of the present invention.
[0009] An object of the present invention is to provide a hydrophobic nanofiber and a method for producing the same. [Means for solving the problem]
[0010] The present invention has the following aspects. [1] At least one hydrogen atom of a hydroxyl group in at least one glucose unit is -COR 1 (R 1 A hydrophobic nanofiber comprising a β-1,3-glucan substituted with ...hydroxybutyric acid group (representing an aliphatic or aromatic hydrocarbon group). [2] The β-1,3-glucan has the following formula (I): TIFF0007640069000001.tif44170 (In formula (I), R 2 each independently represents a hydrogen atom or -COR 1 R 1 represents an aliphatic or aromatic hydrocarbon group, and n represents an integer of 1 or more. 2 At least one of -COR 1 is) The hydrophobic nanofiber according to [1], having a structure represented by the following formula: [3] The β-1,3-glucan has the following formula (II): TIFF0007640069000002.tif39170 (In formula (II), R 2 each independently represents a hydrogen atom or -COR 1 R 1 represents an aliphatic or aromatic hydrocarbon group, and m represents an integer of 1 or more. 2 At least one of -COR 1 The hydrophobic nanofiber according to [1] or [2], having a structure represented by the formula: [4]-COR 1 R in 1 is an aliphatic hydrocarbon group, and the aliphatic hydrocarbon group is a linear or branched aliphatic hydrocarbon group having 1 to 25 carbon atoms. [5] -COR per glucose unit of β-1,3-glucan 1 The hydrophobic nanofiber according to any one of [1] to [4], wherein the number is 1.00 or more. [6] -COR per glucose unit of β-1,3-glucan 1 The hydrophobic nanofiber according to any one of [1] to [5], wherein the number is 2.90 or less. [7] The hydrophobic nanofiber according to any one of [1] to [6], which is used as a fibrous filler. [8] An aggregate of hydrophobic nanofibers according to any one of [1] to [7]. [9] A method for producing a hydrophobic nanofiber according to any one of [1] to [7], At least one hydrogen atom of a hydroxy group in at least one glucose unit is -COR 1 (R 1 A method for producing hydrophobic nanofibers, comprising: immersing an aggregate of hydrophobic nanofibers comprising β-1,3-glucan substituted with a ... linear or branched aliphatic hydrocarbon group (wherein m represents a linear or branched aliphatic hydrocarbon group) in an organic solvent to obtain hydrophobic nanofibers.
[10] The method according to [9], wherein the organic solvent comprises at least one selected from the group consisting of halogenated solvents, protic solvents, and aprotic solvents.
[11] -COR per glucose unit of β-1,3-glucan 1 The method according to [9] or
[10] , wherein the number is 1.00 or more.
[12] -COR per glucose unit of β-1,3-glucan 1 The method according to any one of [9] to
[11] , wherein the number is 2.90 or less. Effect of the Invention
[0011] According to the present invention, a hydrophobic nanofiber and a method for producing the same can be provided. [Brief description of the drawings]
[0012] [Figure 1] 1 is a scanning electron microscope photograph of a hydrophobic nanofiber aggregate after drying. [Diagram 2] FIG. 1 is an explanatory diagram of a method for obtaining hydrophobic nanofibers by defibrating a hydrophobic nanofiber aggregate. [Diagram 3]1A and 1B are scanning probe micrographs of products obtained by immersing hydrophobic nanofiber assemblies 1 and 2 in chloroform, dichloromethane, and DMF, respectively. [Figure 4] 1A and 1B are scanning probe micrographs of the products obtained by immersing hydrophobic nanofibers 3 and 4 in chloroform, dichloromethane, and DMF, respectively. [Diagram 5] 1 shows scanning probe microscope photographs of products obtained by immersing hydrophobic nanofibers 5 to 7 in chloroform, dichloromethane, and DMF, respectively. [Figure 6] 13A and 13B are scanning probe micrographs of the products obtained by immersing hydrophobic nanofibers 8 and 9 in chloroform, dichloromethane, and DMF, respectively. [Figure 7] 1A and 1B are scanning probe micrographs of the products obtained by immersing hydrophobic nanofibers 10 and 11 in chloroform, dichloromethane, and DMF, respectively. [Figure 8] 1A and 1B are scanning probe micrographs of the products obtained by immersing hydrophobic nanofibers 12 in chloroform, dichloromethane, and DMF, respectively. [Figure 9] 1 shows scanning electron microscope photographs of freeze-dried products obtained by immersing hydrophobic nanofiber aggregates 1 to 12 in DMSO. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] An embodiment of the present invention will be described in detail below. The present invention is not limited to the following embodiment, and can be carried out by making appropriate modifications within the scope that does not impair the effects of the present invention.
[0014] [Hydrophobic nanofiber] In the hydrophobic nanofiber according to the present embodiment, the hydrogen atom of at least one hydroxyl group in at least one glucose unit is -COR 1 (R 1The hydrophobic nanofiber contains β-1,3-glucan substituted with β-1,3-glucan (representing an aliphatic or aromatic hydrocarbon group). At least one hydroxy group in at least one glucose unit of the hydrophobic nanofiber is acylated. The hydrophobic nanofiber containing β-1,3-glucan is a novel nanofiber that has not been known before.
[0015] "Hydrophobic nanofiber" means nanofiber that is dispersed in an organic solvent or exists as a gel. The organic solvent in which the hydrophobic nanofiber is dispersed is usually transparent, and may have viscosity if the nanofiber is in a good defibrated state. Because it can be dispersed in an organic solvent, it can be made into a nanofiber that is highly dispersible and easy to knead into hydrophobic resins such as polypropylene and hydrophobic fibers, which has been considered difficult to do in the past. "Hydrophobic nanofibers" are composed of dozens of acylated β-1,3-glucans having a triple helix structure, as described below, and are observed as fibrous materials with fiber diameters on the nanometer scale in scanning electron microscope or scanning probe microscope photographs.
[0016] "β-1,3-glucan" means a polysaccharide having a structure in which glucose is linked by a β-1,3 bond. That is, β-1,3-glucan has a structure in which the 1-position of a β-glucose and the 3-position of another β-glucose form a β-1,3-glucoside bond. The term "β-1,3-glucan" includes β-1,3-glucan and its derivatives. β-1,3-glucan is mainly produced by algae and fungi.
[0017] In β-1,3-glucan, three molecules associate in water to form a triple helix structure, due to the structure in which glucose is linked by β-1,3 bonds. This results in nanofibers with a triple helix structure. In contrast, β-1,4-glucan such as cellulose forms a sheet structure with glucose linked by β-1,4-bonds. Nanofibers of β-1,3-glucan with a triple helix structure have a smaller fiber diameter than cellulose nanofibers, and are therefore expected to have excellent fiber properties such as tensile strength and sustained length. The fact that β-1,3-glucan forms a triple helix structure can be confirmed, for example, by X-ray crystal structure analysis, circular dichroism spectroscopy and visible absorption spectroscopy in the presence of a dye, transmission electron microscope observation, or scanning probe microscope observation.
[0018] β-1,3-glucan can spontaneously form nanofibers in water, so nanofibers can be produced from the raw material using a bottom-up method, which has the advantage that it can be produced using a method that consumes less energy than nanofibers produced using a top-down method in which hydrophobic natural polymers are mechanically pulverized to nanoscale levels.
[0019] β-1,3-glucan that has formed a triple helix structure is in the form of a gel-like mass when collected from water, and in the form of a solid aggregate after drying (Figure 1: Dry solid). This makes it difficult to disperse it in resin. However, it was surprisingly found that β-1,3-glucan, in which the hydrogen atom of at least one hydroxyl group in at least one glucose unit constituting β-1,3-glucan is substituted with an acyl group, forms a triple helix structure in water and forms aggregates, but can be defibrated to form hydrophobic nanofibers by subsequent immersion in an organic solvent (see Figure 2). The "lump product solid" in Figure 2 is -COR 1 This is a precipitate that is produced when β-1,3-glucan substituted with α-hydroxybutyric acid groups is placed in water, and is an aggregate of hydrophobic nanofibers. The reason for this is not clear at this stage, but it is thought that the molecules of the solvent used weaken the relatively weak interactions between the aggregated hydrophobic nanofibers while not affecting the strong interactions between the hydrophobic β-1,3-glucan molecules that make up the nanofibers, resulting in successful defibration and the emergence of hydrophobic nanofibers. It is believed that β-1,3-glucan having acyl groups forms a hierarchical structure. In other words, one molecule is a single-stranded acylated β-1,3-glucan, three molecules associate to form an acylated β-1,3-glucan having a triple helix structure, and several dozens of triple helices are assembled to form hydrophobic nanofibers. Therefore, it is believed that the hydrophobic nanofibers of this embodiment are obtained by immersing an aggregate of hydrophobic nanofibers precipitated in water in an appropriate solvent, which defibrates them to the hydrophobic nanofiber stage (i.e., without defibrating them to a lower level) and obtaining them as nanofibers.
[0020] The hydrophobic nanofiber aggregate, which is a gel-like mass, can be defibrated in an organic solvent even in a dry state to form hydrophobic nanofibers, so the gel-like mass can be dried and easily stored and transported as a solid "hydrophobic nanofiber base." In contrast, cellulose nanofibers can only stably maintain the nanofiber form when dispersed in a solvent, so they must be stored and transported in liquid form.
[0021] -COR 1 R in 1 is an aliphatic or aromatic hydrocarbon group. The aliphatic hydrocarbon group preferably has 1 to 25 carbon atoms, more preferably has 1 to 20 carbon atoms, even more preferably has 1 to 15 carbon atoms, still more preferably has 1 to 12 carbon atoms, particularly preferably has 1 to 8 carbon atoms, and even more particularly preferably has 1 to 5 carbon atoms. -COR 1 R in 1The hydrophobicity can be further increased by making is an aliphatic hydrocarbon group having 1 to 25 carbon atoms. The aromatic hydrocarbon group preferably has 6 to 25 carbon atoms, more preferably has 6 to 20 carbon atoms, even more preferably has 6 to 15 carbon atoms, and still more preferably has 6 to 12 carbon atoms.
[0022] -COR 1 R in 1 As R, one type of aliphatic or aromatic hydrocarbon group may be contained, or two or more types of aliphatic or aromatic hydrocarbon groups may be contained. 1 When the alkyl group has two or more types of aliphatic or aromatic hydrocarbon groups, from the viewpoint of facilitating the formation of a triple helix structure, it is preferable that all of the aliphatic or aromatic hydrocarbon groups have 10 or less carbon atoms (more preferably 8 or less carbon atoms).
[0023] The aliphatic hydrocarbon group may be linear, branched, or have a cyclic structure. When the carbon number is 2 or more, the group may be an alkyl group consisting of a carbon-carbon single bond, or an alkenyl or alkynyl group containing one or more double or triple bonds. 1 R in 1 is preferably a linear or branched alkyl group, more preferably a linear alkyl group, from the viewpoints of ease of acylation and ease of formation of a triple helix structure.
[0024] Examples of the linear or branched aliphatic hydrocarbon group include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an i-butyl group, an s-butyl group, a t-butyl group, an n-pentyl group, a vinyl group, a 1-propenyl group, a 2-propenyl group, a 1-butenyl group, a 2-butenyl group, a 3-butenyl group, a 1-methyl-2-propenyl group, a 2-methyl-2-propenyl group, a 1-pentenyl group, a 2-pentenyl group, a 3-pentenyl group, a 4-pentenyl group, a 1-methyl-2-butenyl group, and a 2-methyl-2-butenyl group. , 1-ethylhexyl group, 1-ethylheptyl group, 1-ethyloctyl group, 1-ethylnonyl group, 1-propylpentyl group, 1-propylhexyl group, 1-propylheptyl group, 1-propyloctyl group, 1-butylpentyl group, 1-butylhexyl group, 1-butylheptyl group, 2-ethylhexyl group, 2-ethylheptyl group, 2-ethyloctyl group, 2-ethylnonyl group, 2-propylpentyl group, 2-propylhexyl group, 2-propylheptyl group, 2-propyloctyl group, etc. It is preferable that the alkyl group has one or more linear or branched aliphatic hydrocarbon groups selected from these. Examples of the aromatic hydrocarbon group include a phenyl group and a naphthyl group. Among these, from the viewpoints of high acylation efficiency and ease of forming a triple helix structure, one or more groups selected from a methyl group, an ethyl group, and a propyl group are preferred.
[0025] In one embodiment, the -COR per glucose unit of β-1,3-glucan 1 The number of -COR per glucose unit of β-1,3-glucan (hereinafter also referred to as "degree of substitution") is preferably 1.00 or more and preferably 2.90 or less. 1 The number is more preferably from 1.10 to 2.80, even more preferably from 1.10 to 2.70, and particularly preferably from 1.15 to 2.60. -COR per glucose unit of β-1,3-glucan 1 By making the number of -COR per glucose unit of β-1,3-glucan 1.00 or more, it is possible to obtain hydrophobic nanofibers. 1By making the number 2.90 or less, the fiber can be more easily defibrated in an organic solvent. In one embodiment, the -COR per glucose unit of β-1,3-glucan 1 The number is between 1.16 and 2.52.
[0026] The degree of substitution can be adjusted by adjusting the temperature and / or time in the acylation reaction, adjusting the amount of the acylating agent charged, etc. For example, the degree of substitution can be increased by increasing the amount of the acylating agent, increasing the reaction temperature, or lengthening the reaction time, while the degree of substitution can be decreased by decreasing the amount of the acylating agent, decreasing the reaction temperature, or shortening the reaction time.
[0027] In one embodiment, the β-1,3-glucan has the formula (I): TIFF0007640069000003.tif44170 It has a structure represented by the following formula: In formula (I), R 2 each independently represents a hydrogen atom or -COR 1 R 1 represents an aliphatic or aromatic hydrocarbon group, and n represents an integer of 1 or more. 2 At least one of -COR 1 -COR 1 The type and degree of substitution are as described above. Examples of β-1,3-glucans having the structure of formula (I) include laminaran, schizophyllan, pachyman, lentinan, curdlan, and paramylon.
[0028] In one embodiment, the β-1,3-glucan has the formula (II): TIFF0007640069000004.tif39170 It has a structure represented by the following formula: In formula (II), R 2 each independently represents a hydrogen atom or -COR 1 R 1 represents an aliphatic or aromatic hydrocarbon group, and m represents an integer of 1 or more.2 (Preferably, R in the repeating unit having a number represented by an integer m) 2 ) is at least -COR 1 -COR 1 The type and degree of substitution are as described above. Examples of β-1,3-glucans having the structure of formula (II) include paramylon and curdlan. Paramylon is a chain of about 2000 glucose units, and curdlan is about twice as long. Therefore, in the case of paramylon, the degree of polymerization (n or m) in formulas (I) and (II) is about 1000. In the case of curdlan, the degree of polymerization (n or m) is about 2000.
[0029] β-1,3-glucan may contain a structure in which glucose is linked by β-1,6 bonds in addition to a structure in which glucose is linked by β-1,3 bonds. The β-1,3-glucan may have a structure in which a branched chain formed by β-1,6-glucosidic bonds is bound to a main chain linked by β-1,3-glucosidic bonds.
[0030] Examples of β-1,3-glucans include laminaran (a linear polysaccharide containing β-1,3 and β-1,6 bonds), schizophyllan (a branched polysaccharide containing β-1,3 and β-1,6 bonds), pachyman (a polysaccharide whose main chain is composed of β-1,3 bonds and has 3 to 6 side chains per molecule), lentinan (a polysaccharide whose main chain is composed of β-1,3 bonds and has 2 side glucose molecules for every 5 glucose molecules in the main chain), curdlan (a polysaccharide that is almost linear but has one side chain for approximately 200 glucose units), and paramylon (a linear polysaccharide that has no side glucose molecules). Paramylon is an energy storage substance synthesized and accumulated by Euglena (green algae), a type of microalgae, and exists as egg-shaped micro-sized particles (paramylon particles) within the cells of Euglena.
[0031] In one embodiment, from the viewpoint of easily forming a triple helix structure in water, it is preferable that there is less than one branched chain per three hydroxyl groups of the glucose residues that constitute the β-1,3-glucan, and it is more preferable that the β-1,3-glucan has no branched chains, i.e., is composed only of β-1,3-glucosidic bonds.
[0032] The number of branched chains present in a β-1,3-glucan molecule can be determined by enzymatically hydrolyzing the β-1,3-glucan and then measuring the absorption spectrum of the resulting hydrolyzate (Osaka University Graduate School of Technology Department Report, Vol. 16, p. 99 (2008)).
[0033] In one embodiment, the average fiber length of the hydrophobic nanofibers is preferably 0.1 to 100 μm, more preferably 0.5 to 100 μm, further preferably 1 to 100 μm, and particularly preferably 10 to 100 μm. The average fiber diameter of the hydrophobic nanofibers is preferably 10 to 500 nm, more preferably 10 to 200 nm, further preferably 10 to 100 nm, and particularly preferably 10 nm or more and less than 100 nm. In one embodiment, the average fiber diameter of the hydrophobic nanofibers is 50 nm or less. The average fiber length and the average fiber diameter are average values calculated by measuring the fiber length and diameter of 10 nanofibers using a scanning probe microscope (SPM). Furthermore, because β-1,3-glucan containing acyl groups has strong intermolecular interactions, even if one attempts to obtain nanofibers by mechanically crushing it, the resulting fibers often have large fiber diameters on the order of micrometers.
[0034] (Application) Hydrophobic nanofibers have high dispersibility in hydrophobic environments such as resins and organic solvents, and therefore can be preferably used as a fibrous filler to be added to resins, rubbers, etc. They can also be preferably used as a material for high-performance membranes such as oxygen barrier membranes.
[0035] [Hydrophobic nanofiber assembly] The hydrophobic nanofiber aggregate according to this embodiment is an aggregate of the above-mentioned hydrophobic nanofibers. The hydrophobic nanofiber aggregate is precipitated as a gel-like substance by placing a reaction solution of acylated β-1,3-glucan in a poor solvent (e.g., water).
[0036] The form of the hydrophobic nanofiber aggregate is not particularly limited. For example, the solid obtained as a precipitate in water is a gel swollen in water, and the swollen gel may be dried to form a dry solid. Furthermore, the swollen gel may be cast on a substrate and dried to form a film.
[0037] [Method of manufacturing hydrophobic nanofibers] The method for producing a hydrophobic nanofiber according to the present embodiment is characterized in that the hydrogen atom of at least one hydroxyl group in at least one glucose unit is -COR 1 (R 1 The method includes immersing an aggregate of hydrophobic nanofibers (hereinafter also referred to as a "hydrophobic nanofiber aggregate") containing β-1,3-glucan substituted with ...
[0038] The hydrophobic nanofiber aggregate exists as a gel-like mass when collected from water, and as a solid after drying. By immersing the hydrophobic nanofiber in an organic solvent, the hydrophobic nanofiber aggregate is defibrated and dispersed, resulting in hydrophobic nanofibers consisting of dozens of β-1,3-glucans with triple helix structures (immersion method). Since it can be dispersed in an organic solvent, it can also be dispersed in hydrophobic substances such as resins.
[0039] "β-1,3-glucan", "-COR 1 The "hydrophobic nanofiber" and "hydrophobic nanofiber aggregate" are as described above.
[0040] As the organic solvent, a solvent is selected that can weaken the relatively weak interactions due to hydrogen bonds between β-1,3-glucans in the aggregate nanofibers (hydrophobic nanofiber aggregates) and defibrate them, but that does not affect the strong interactions between the hydrophobized β-1,3-glucan molecules and does not dissolve the nanofibers themselves. Examples of organic solvents include halogenated solvents, protic solvents, and aprotic solvents. Examples of halogenated solvents include chloroform and dichloromethane. Examples of protic solvents include alcohols such as methanol. Examples of aprotic polar solvents include N,N-dimethylformamide (DMF), dimethylsulfoxide (DMSO), ethyl acetate, acetonitrile, tetrahydrofuran, N,N-dimethylacetamide, and pyridine. Ionic liquids such as 1-allyl-3-methylimidazolium chloride can also be used. In one embodiment, the organic solvent comprises one or more selected from the group consisting of chloroform, dichloromethane, DMF, and DMSO. The organic solvent contains one or more selected from the above-mentioned solvents in an amount of preferably 50% by mass or more, more preferably 80% by mass or more, even more preferably 95% by mass or more, and particularly preferably 98% by mass or more. In one embodiment, the organic solvent consists of one or more of the above-mentioned organic solvents.
[0041] Types of organic solvents and acyl groups (-COR 1 The combination of the degree of substitution of the acyl group with the degree of substitution of the acyl group is not limited. For example, when the degree of substitution of the acyl group is 1.0 to 1.5, the fiber may be defibrated in an aprotic polar solvent such as N,N-dimethylformamide (DMF). When the degree of substitution of the acyl group is more than 1.5, the fiber may be defibrated in a halogen-based solvent such as dichloromethane or in an aprotic polar solvent.
[0042] "Soaking" means that the hydrophobic nanofiber aggregate is placed in the organic solvent so that the entirety of the hydrophobic nanofiber aggregate is soaked in the organic solvent. Therefore, the amount of the organic solvent used may be an amount that can soak the entirety of the hydrophobic nanofiber aggregate. For example, the amount of the organic solvent used may be 1 to 10 mL per 50 mg of the dry solid of the hydrophobic nanofiber aggregate. The immersion conditions are preferably 20 to 40° C. for 1 to 50 hours, and more preferably 30 to 40° C. for 10 to 30 hours.
[0043] In one embodiment, the immersion is performed while stirring. By immersing the fibrous material while stirring, defibration is more likely to proceed. Stirring is preferably performed at 20 to 40° C. for 10 to 300 minutes, more preferably at 30 to 40° C. for 60 to 300 minutes, using a magnetic stirrer or the like as necessary. After stirring, the solvent can be removed by centrifugation, filtration, or the like to obtain hydrophobic nanofibers in an unraveled state. In order to prevent the shape change and aggregation of the hydrophobic nanofibers, the hydrophobic nanofibers can be stored, transported, and kneaded with resins, etc., without removing the solvent.
[0044] The method for producing a hydrophobic nanofiber according to this embodiment may include a step of washing and / or drying the obtained hydrophobic nanofiber, if necessary. The washing and / or drying can be carried out by a known method. For example, washing can be carried out by stirring in a solvent such as a lower alcohol such as methanol or ethanol, or acetone at 20 to 40°C for 5 to 30 minutes. After washing, the solvent is removed by a known method. Drying can be carried out, for example, by air drying at 50 to 80°C for 1 to 24 hours and / or by heating and drying under vacuum at 30 to 60°C for 1 to 6 hours.
[0045] The hydrophobic nanofiber aggregate may be one that has been produced in advance, or may be produced by the following steps (i) to (iii) and used. Step (i) dissolving a raw material β-1,3-glucan in an organic solvent; adding an acylating agent having an aliphatic or aromatic hydrocarbon group to the solution obtained in step (ii)(i) and reacting the β-1,3-glucan with the acylating agent; Step (iii) Putting the reaction product into water to obtain a hydrophobic nanofiber aggregate.
[0046] (Step (i): Dissolution step) In step (i), the raw material β-1,3-glucan is dissolved in an organic solvent. By dissolving the raw material β-1,3-glucan in an organic solvent, a single-stranded β-1,3-glucan is obtained. By obtaining the single-stranded β-1,3-glucan, an acyl group can be efficiently introduced into the glucose unit of the β-1,3-glucan in step (ii). Conventionally, when hydrophobizing cellulose nanofibers, it was necessary to use a heterogeneous reaction in which hydrophobic groups were directly introduced into the nanofibers. As a result, the introduction rate of hydrophobic groups was low, and the types of substituents that could be introduced were limited. In contrast, single-stranded β-1,3-glucan can be formed by dissolving β-1,3-glucan in an aprotic polar organic solvent such as N,N-dimethylacetamide (DMAc) or an ionic fluid such as 1-butyl-3-methylimidazolium chloride. Since single-stranded β-1,3-glucan can be hydrophobized in a homogeneous reaction system (dissolved in a solvent), the introduction rate of hydrophobic groups is high and the introduction rate of hydrophobic groups can be easily controlled.
[0047] From the viewpoint of reducing the environmental load, the raw material β-1,3-glucan is preferably derived from a living organism, more preferably from a plant. In particular, it is preferable to use β-1,3-glucan isolated from microalgae that synthesize β-1,3-glucan within the cells as the raw material. As the microalgae, Euglena (a microalgae belonging to the Euglenophyta) is preferable. This is because Euglena is easy to culture, has a fast growth cycle, and accumulates a large amount of paramylon particles within the cells as a photosynthetic product. The paramylon synthesized and accumulated by Euglena is a β-1,3-glucan that is usually formed by β-1,3 bonds between 2000 glucose molecules. β-1,3-glucans such as paramylon can be separated from microalgae by a conventional method.
[0048] The organic solvent is selected from those capable of dissolving the raw material β-1,3-glucan. Examples of the organic solvent include aprotic polar organic solvents such as N,N-dimethylacetamide (DMAc) and N,N-dimethylsulfoxide (DMSO); ionic fluids such as 1-butyl-3-methylimidazolium chloride and 1-allyl-3-methylimidazolium chloride; and the like. A mixed solvent such as DMSO / DMF can also be used. The organic solvent contains one or more selected from these in an amount of preferably 50% by mass or more, more preferably 80% by mass or more, still more preferably 95% by mass or more, and particularly preferably 98% by mass or more. The organic solvent may contain a salt such as lithium chloride or TBAF (tetrabutylammonium fluoride) as necessary to stabilize the β-1,3-glucan in a single-chain form. The amount of the organic solvent used is not limited, and can be, for example, 10 to 500 mL per 1 g of the raw material β-1,3-glucan.
[0049] Dissolution can be carried out by stirring a mixture of the raw material β-1,3-glucan and organic solvent using a known device such as a magnetic stirrer, preferably under a nitrogen atmosphere, at 100 to 120°C for 30 to 60 minutes until the solution becomes transparent (until it becomes a homogeneous solution).
[0050] (Step (ii): Acylation step) In step (ii), an acylating agent having an aliphatic or aromatic hydrocarbon group is added to the solution (homogeneous solution) obtained in (i) to react the β-1,3-glucan with the acylating agent. Prior to step (ii), the homogeneous solution obtained in step (i) may be allowed to cool to room temperature (e.g., 20 to 30°C).
[0051] In one embodiment, the acylating agent comprises a chloride or anhydride of a carboxylic acid having an aliphatic or aromatic hydrocarbon group. The acylating agent is represented by the following formula (III): R 1 -COOH (III) (However, R 1 is an aliphatic or aromatic hydrocarbon group) Preferably, the chloride or anhydride of a carboxylic acid represented by R 1 The type of -COR of β-1,3-glucan that constitutes the hydrophobic nanofiber described above 1 R in 1 is the same as:
[0052] Examples of carboxylic acids satisfying formula (III) include aliphatic monocarboxylic acids such as acetic acid, propionic acid, butanoic acid (butyric acid), pentanoic acid (valeric acid), 3-methylbutanoic acid (isovaleric acid), hexanoic acid (caproic acid), heptanoic acid (enanthic acid), 2-ethylhexanoic acid, octanoic acid (caprylic acid), nonanoic acid (pelargonic acid), decanoic acid (capric acid), dodecanoic acid (lauric acid), tetradecanoic acid (myristic acid), hexadecanoic acid (paltimic acid), heptadecanoic acid (margaric acid), and octadecanoic acid (stearic acid), and aromatic monocarboxylic acids such as benzoic acid. Among these, from the viewpoint of high acylation efficiency and ease of forming a triple helix structure, it is preferable to contain one or more chlorides or anhydrides selected from acetic acid, propionic acid, and butanoic acid (butyric acid).
[0053] The amount of the acylating agent used is preferably 2 to 20 moles, more preferably 1 to 6 moles, per mole of the raw material β-1,3-glucan used in step (i). When reaction products with different degrees of substitution are withdrawn stepwise during the reaction, the acylating agent can be used in an amount of 20 to 50 moles (e.g., 40 times by mole) per mole of the raw material β-1,3-glucan.
[0054] The reaction (acylation reaction) can be carried out by reacting the above-mentioned acylation agent in a homogeneous solution in which single-stranded β-1,3-glucan is dissolved, in the presence of a Lewis acid such as lithium chloride or a base such as pyridine.
[0055] The reaction conditions such as reaction temperature and reaction time are appropriately set in consideration of the type of acylating agent used, the desired degree of substitution, etc. For example, when acetic anhydride is used as the acylating agent, a reaction product having an acyl group substitution degree of 1.00 or more per glucose unit can be obtained by stirring at 70 to 100°C for 45 minutes to 18 hours. To increase the substitution degree, the reaction temperature can be increased or the reaction time can be extended, and to decrease the substitution degree, the reaction temperature can be decreased or the reaction time can be shortened.
[0056] The reaction product of the acylation reaction (acylated β-1,3-glucan) is obtained in a state dissolved in the organic solvent.
[0057] (Step (iii): association step) In step (iii), the reaction solution containing the reaction product obtained in step (ii) is poured into water to obtain a precipitate. When the reaction mixture obtained in step (ii) is poured into water, the acylated single-stranded β-1,3-glucan associates through intermolecular interactions to form a triple helix structure consisting of three molecules, and a white precipitate is obtained. The white precipitate is composed of an aggregate of hydrophobic nanofibers having a triple helix structure.
[0058] The association conditions are not particularly limited, and the mixture is immersed in water or stirred in water at 20 to 30° C. Usually, when the reaction solution is poured into water, a gel-like white precipitate appears immediately. The precipitate can then be obtained by recovering it from the water by centrifugation, decantation, or the like.
[0059] After the step (iii), a step of washing the precipitate may be carried out as necessary. The washing can be carried out by a known method. After washing, the solvent is removed by a known method.
[0060] The hydrophobic nanofiber aggregate obtained in step (iii) is in a swollen gel-like solid state (hereinafter also referred to as "swollen gel" or "lump nanofibers") when recovered from water. The hydrophobic nanofiber aggregate can also be in a dry solid state by drying the swollen gel. Furthermore, the swollen gel can also be cast on a substrate and dried to form a film-shaped hydrophobic nanofiber aggregate. The hydrophobic nanofibers obtained as described above are immersed in an organic solvent and stirred to obtain hydrophobic nanofibers (fibrillation step). EXAMPLES
[0061] The present invention will be described in more detail below with reference to examples, but the interpretation of the present invention is not limited to these examples.
[0062] Hydrophobic nanofiber aggregates containing acetyl paramylon with different degrees of acyl group substitution were produced as follows. The synthesis scheme of acetyl paramylon is as follows: TIFF0007640069000005.tif30170
[0063] [Hydrophobic nanofiber assembly 1] A mixture of paramylon (2.002 g, 12.347 mmol (based on glucose units)), N,N-dimethylacetamide (DMAc, 100 mL), and lithium chloride (LiCl, 1.617 g, 38.146 mmol) was stirred at 102°C for 30 minutes under a nitrogen atmosphere to obtain a homogeneous solution (step (i)). The solution was allowed to cool to room temperature, after which DMAc (200 mL), pyridine (34 mL, 0.422 mol), and acetic anhydride (49 mL, 0.518 mol) were added, and the mixture was mechanically stirred at 70° C. (step (ii)). At the point 45 minutes after the start of the reaction, 200 mL of the reaction solution was extracted from the reaction mixture with a syringe, and this was poured into 250 mL of water to cause a white precipitate (precipitate) (step (iii)). The white precipitate was separated by centrifugation (2600×g, room temperature, 3 minutes), and then dispersed in 200 mL of methanol and washed multiple times by stirring overnight, etc., to obtain a white solid (washing step). The solid was collected by centrifugation, air-dried overnight, and then heated and dried under vacuum (60°C, 7 hours) to obtain hydrophobic nanofiber aggregate 1 (1.002 g, yield 73.4%).
[0064] 1 The synthesis of the target product was confirmed by HNMR and FT-IR. 1 H-NMR (1.0N NaOD / D 2 O)δ(ppm):4.72(m),3.94-3.49(m),1.92(s) FT-IR (cm -1 ):3437,2912,1732,1702,1369,1227,1038,888
[0065] In the following, hydrophobic nanofibers were produced by changing the amount of raw material paramylon, the amount of solvent used, and / or the reaction time and reaction temperature.
[0066] [Hydrophobic nanofiber assembly 2] A mixture of paramylon (4.002 g, 24.681 mmol (based on glucose units)), N,N-dimethylacetamide (DMAc, 200 mL), and lithium chloride (LiCl, 3.143 g, 74.145 mmol) was stirred at 115° C. for 30 minutes under a nitrogen atmosphere to obtain a homogeneous solution (step (i)). The solution was allowed to cool to room temperature, after which DMAc (400 mL), pyridine (70 mL, 0.869 mol), and acetic anhydride (96 mL, 1.016 mol) were added, and the mixture was mechanically stirred at 69° C. (step (ii)). Acetylparamylon was obtained as a solid from this reaction mixture by the following method (step (iii)). Two hours after the start of the reaction, 150 mL of the reaction solution was extracted from the reaction mixture using a syringe, and then poured into 200 mL of water to cause a white precipitate (precipitate, an aggregate of hydrophobic nanofibers). The white precipitate was separated by centrifugation (2600×g, room temperature, 3 minutes), and then dispersed in 200 mL of methanol and washed multiple times by stirring overnight, etc., to obtain a white solid (washing step). This solid was collected by centrifugation, air-dried overnight, and then heated and dried under vacuum (60°C, 5 hours) to obtain hydrophobic nanofiber aggregate 2 (753 mg, yield 73.4%).
[0067] [Hydrophobic nanofiber assembly 3] Hydrophobic nanofiber aggregate 3 (727 mg, yield 55.4%) was obtained in the same manner as for hydrophobic nanofiber aggregate 1, except that step (iii) was applied to the remaining reaction liquid 1.5 hours after the start of the reaction in producing hydrophobic nanofiber aggregate 1.
[0068] 1 The synthesis of the target product was confirmed by HNMR and FT-IR. 1 H-NMR (1.0N NaOD / D 2 O)δ(ppm):4.72(m),3.94-3.44(m),1.93(s) FT-IR (cm -1):3441,2908,1733,1646,1369,1227,1035,894
[0069] [Hydrophobic nanofiber assemblies 4-7] Hydrophobic nanofiber aggregates 4 to 7 were obtained in the same manner as for hydrophobic nanofiber aggregate 2, except that step (iii) was applied to the reaction liquid sampled 3, 4.5, and 5.5 hours after the start of the reaction in the production method of hydrophobic nanofiber aggregate 2, and to the remaining reaction liquid 6 hours after the start of the reaction. The yields were as follows. Hydrophobic nanofiber assembly 4: 836 mg, yield 75.3% Hydrophobic nanofiber assembly 5: 459 mg, yield 40.7% Hydrophobic nanofiber assembly 6: 898 mg, yield 75.6% Hydrophobic nanofiber assembly 7: 1.253 g, yield 94.7%
[0070] Regarding hydrophobic nanofiber assemblies 2, 4 to 7, 1 The synthesis of the target product was confirmed by HNMR and FT-IR. (Hydrophobic nanofiber assembly 2) 1 H-NMR (1.0N NaOD / D 2 O)δ(ppm):4.72(m),3.94-3.44(m),1.92(s) FT-IR (cm -1 ):3436,2907,1737,1652,1369,1226,1035,887 (Hydrophobic nanofiber assembly 4) 1 H-NMR (1.0N NaOD / D 2 O)δ(ppm):4.72(m),3.94-3.44(m),1.92(s) FT-IR (cm -1 ):3447,2908,1733,1647,1369,1219,1028,894 (Hydrophobic nanofiber assembly 5) 1 H-NMR (1.0N NaOD / D2 O)δ(ppm):4.72(m),3.94-3.44(m),1.92(s) FT-IR (cm -1 ):3444,2906,1735,1647,1369,1221,1029,893 (Hydrophobic nanofiber assembly 6) 1 H-NMR (1.0N NaOD / D 2 O)δ(ppm):4.72(m),3.94-3.45(m),1.92(s) FT-IR (cm -1 ):3445,2921,1733,1370,1217,1029,892 (Hydrophobic nanofiber assembly 7) 1 H-NMR (1.0N NaOD / D 2 O)δ(ppm):4.72(m),3.94-3.44(m),1.92(s) FT-IR (cm -1 ):2923,1734,1647,1369,1217,1030,893
[0071] [Hydrophobic nanofiber assembly 8] A mixture of paramylon (9.999 g, 61.669 mmol (based on glucose units)), N,N-dimethylacetamide (DMAc, 500 mL), and lithium chloride (LiCl, 7.865 g, 185.522 mmol) was stirred at 103° C. for 30 minutes under a nitrogen atmosphere to obtain a homogeneous solution (step (i)). The solution was allowed to cool to room temperature, after which DMAc (1.0 L), pyridine (168 mL, 2.085 mol), and acetic anhydride (240 mL, 2.539 mol) were added, and the mixture was mechanically stirred at 104° C. (step (ii)). 1.5 hours after the start of the reaction, 250 mL of the reaction solution was extracted from the reaction mixture using a syringe, and then poured into 250 mL of water to cause a white precipitate. The white precipitate was separated by centrifugation (2600×g, room temperature, 3 minutes), and then dispersed in 300 mL of methanol and washed by stirring for 1.5 hours to obtain a yellow precipitate (washing step). The solid was collected by centrifugation and air-dried for 2.5 hours. This washing process was repeated twice. The yellow solid was dried by heating under vacuum (60°C, 2 hours) to obtain hydrophobic nanofiber aggregate 8 (1.521 g, 72.3% yield).
[0072] 1 The synthesis of the target product was confirmed by HNMR and FT-IR. 1 HNMRδ(ppm):4.72(m),3.94-3.45(m),1.92(s) FT-IR (cm -1 ):1734,1371,1213,1029,891
[0073] [Hydrophobic nanofiber assemblies 9-12] Hydrophobic nanofiber aggregates 9 to 12 were obtained in the same manner as for producing hydrophobic nanofiber aggregate 8, except that step (iii) was applied to the reaction liquid withdrawn 3, 4, and 5 hours after the start of the reaction in the production of hydrophobic nanofiber aggregate 8, and to the remaining reaction liquid 24 hours after the start of the reaction. The yields were as follows. Hydrophobic nanofiber assembly 9: 1.729 g, yield 80.3% Hydrophobic nanofiber assembly 10: 1.763 g, yield 81.7% Hydrophobic nanofiber assembly 11: 1.848 g, yield 85.0% Hydrophobic nanofiber assembly 12: 6.612 g, yield 77.9%
[0074] 1 The synthesis of the target product was confirmed by HNMR and FT-IR. (Hydrophobic nanofiber assembly 9) 1 H-NMR (1.0N NaOD / D 2 O)δ(ppm):4.72(m),3.94-3.45(m),1.92(s) FT-IR (cm -1 ):1733,1372,1210,1028,894 (Hydrophobic nanofiber assembly 10) 1 H-NMR (1.0N NaOD / D 2 O)δ(ppm):4.72(m),3.94-3.44(m),1.92(s) FT-IR (cm -1 ):1733,1371,1211,1032,893 (Hydrophobic nanofiber assembly 11) 1 H-NMR (1.0N NaOD / D 2 O)δ(ppm):4.72(m),3.94-3.44(m),1.92(s) FT-IR (cm -1 ):1735,1371,1212,1032,893 (Hydrophobic nanofiber assembly 12) 1 H-NMR (1.0N NaOD / D 2 O)δ(ppm):4.72(m),3.94-3.46(m),1.92(s) FT-IR (cm -1 ):1734,1368,1212,1030,894
[0075] [Observation and Measurement] (degree of substitution) The degree of acylation (acetylation) of the hydrophobic nanofiber assemblies 1 to 12 was determined by the 1 The results were determined by measuring H-NMR. Specifically, the ratio of the integral value derived from the methyl group of the acyl group to the total integral value of the hydrogen atom derived from glucose was used as the basis for the determination. The results are shown in Table 1. ace As expected, longer reaction times and higher reaction temperatures resulted in higher degrees of substitution. [Table 1]
[0076] (Scanning Electron Microscope (SEM) Observation-1) Hydrophobic nanofiber aggregates 1 to 12 (solids obtained by drying the gels produced by pouring each reaction solution into water) were observed using a scanning electron microscope (JEOL Ltd., JSM-6060). The observation sample was fixed onto a metal stage with conductive double-sided carbon tape. Observations were performed under high vacuum at an accelerating voltage of 2.5 kV. Figures 1(a) to (l) show SEM photographs of hydrophobic nanofiber aggregates 1 to 12, respectively. As shown in Figure 1, the fibers of the hydrophobic nanofiber aggregates 1 to 12 are aggregated together. In addition, all of the hydrophobic nanofiber aggregates 1 to 12 contain nanofibers with a fiber diameter of 100 nm or less and a length of several μm. Therefore, acetyl paramylon naturally forms nanofibers regardless of the degree of substitution.
[0077] (defibration process) Hydrophobic nanofiber aggregates 1 to 12 (approximately 50 mg) were immersed in 2.0 mL each of chloroform, dichloromethane, DMF, and DMSO for 24 hours. Excess solvent was then removed by decantation. The solid obtained was left for 1 minute (dichloromethane, chloroform) or the surface was wiped with filter paper to remove the solvent (DMF and DMSO) remaining on the surface, and the product was obtained.
[0078] (Scanning Probe Microscope (SPM) Observation) To confirm whether nanofibers were formed in the product obtained in the defibration process, the products obtained by immersing in chloroform, dichloromethane, and DMF were observed by scanning probe microscopy (SPM). Observation of the product obtained by immersing in DMSO will be described later. SPM samples were prepared from the dispersion used in the defibration process or from a 100-fold diluted dispersion. If the dispersion formed a soft gel, the SPM sample was prepared by placing 10 μL of the gel on a freshly cleaved mica surface and allowing the solvent to evaporate at room temperature (air drying). If the dispersion was not a soft gel but only a small portion of the solid was dissolved, the SPM sample was prepared by removing approximately 100 μL from a uniform portion of the dispersion, placing it on the mica surface, and allowing the solvent to evaporate at room temperature (air drying). SPM observations were performed at room temperature using a 20 μm scanner (Seiko Instruments SPA-400) and a Seiko Instruments DF-20 cantilever (length 225 μm; spring constant 12 N / m; frequency 124 kHz). For each sample surface, tapping mode measurements (scan speed 0.2-1.0 Hz) were performed on at least five different measurement areas (20 μm × 20 μm).
[0079] Figures 3 to 8 show SPM photographs of the products obtained by immersing hydrophobic nanofiber assemblies 1 to 12 in chloroform, dichloromethane, and DMF, respectively. When the dispersion in the organic solvent forms a soft gel, the SPM photographs show a fine structure derived from the gel. When a soft gel is not formed, the SPM photographs show a fine structure derived from the dissolved product or well-dispersed product solid.
[0080] 3 to 8, nanofibers were formed in which each fiber was dissolved in at least one solvent selected from chloroform, dichloromethane, and DMF at various degrees of substitution. The details are described below.
[0081] The hydrophobic nanofiber aggregate 1 could be defibrated into linear hydrophobic nanofibers with an average fiber diameter of 100 nm and an average fiber length of 4 μm by immersion in DMF (Figure 3(a3)).
[0082] The hydrophobic nanofiber aggregate 2 could be defibrated into hydrophobic nanofibers with an average fiber diameter of 20 to 100 nm and an average fiber length of 2 μm by immersion in DMF (Fig. 3(b4)). As shown in Fig. 3(b2,b3), it could be defibrated into hydrophobic nanofibers with an average fiber diameter of 50 nm and an average fiber length of 0.5 μm by immersion in dichloromethane.
[0083] The hydrophobic nanofiber aggregate 3 was defibrated into nanofibers with an average fiber diameter of 100 nm and an average fiber length of several μm or more by immersion in chloroform (Figure 4(c1)). Since the size of this nanofiber is almost the same as that of the nanofiber shown in Figure 1, immersion in chloroform can defibrate the nanofibers from the hydrophobic nanofiber aggregate without affecting the fiber dimensions. As shown in Figures 4(c2) and (c3), by immersing in dichloromethane, the hydrophobic nanofiber aggregate 3 was able to be defibrated into nanofibers with an average fiber diameter of 50 nm and an average fiber length of 0.5 µm. By immersing the hydrophobic nanofiber assembly 3 in DMF, a fiber structure with an average fiber diameter of 30 nm was obtained (Figure 4(c4)).
[0084] For the hydrophobic nanofiber assembly 4, nanofibers with an average fiber diameter of 30 nm were obtained by immersing in DMF (Figure 4(d4)).
[0085] For hydrophobic nanofiber aggregate 5, the product prepared from the dispersion immersed in DMF formed a fibrous network with a minimum diameter of 30 nm (Figure 5(e3)), suggesting that nanofibers can be produced from hydrophobic nanofiber aggregate 5 by immersion in DMF.
[0086] Regarding the hydrophobic nanofiber aggregate 6, although the image of the product prepared from the dispersion immersed in DMF was somewhat unclear, nanofibers with an average fiber diameter of 30 nm and an average fiber length of 200 nm were observed, suggesting that nanofibers can be produced from the hydrophobic nanofiber aggregate 6 by immersion in DMF (Figure 5(f3)).
[0087] For the hydrophobic nanofiber aggregate 7, no nanofiber structure was obtained when it was immersed in any of chloroform, dichloromethane, and DMF. However, as described later, it was suggested that it could be defibrated into hydrophobic nanofibers by immersing it in DMSO.
[0088] The hydrophobic nanofiber aggregate 8 could be defibrated into nanofibers with an average fiber diameter of 30 nm by immersion in dichloromethane (Figures 6(h2) and (h3)).
[0089] When the hydrophobic nanofiber aggregate 9 was immersed in dichloromethane, nanofibers with an average diameter of 40 nm were observed (Figure 6(i2)). When a sample of this dispersion was diluted 100 times, nanofibers with an average fiber length of 1 μm or less and an average fiber diameter of 20 nm were obtained (Figure 6(i3)). In addition, in Figure 6(i3), nanofibers with a diameter of 20 nm are aggregated. Since the shape of the nanofibers is different from the nanofibers with a diameter of about 100 nm seen in the hydrophobic nanofiber aggregate before immersion, and the nanofibers have a diameter of 20 nm, it is believed that by immersing in dichloromethane, the hydrophobic nanofiber aggregate with a diameter of 100 nm was defibrated down to the hydrophobic nanofibers of the next lower layer. When the hydrophobic nanofiber aggregate 9 was immersed in DMF, nanofibers with an average fiber diameter of 20 nm were confirmed (Figure 6 (i4)), indicating that the hydrophobic nanofiber aggregate 9 can be defibrated into nanofibers by immersion in DMF.
[0090] When the hydrophobic nanofiber aggregate 10 was immersed in chloroform, nanofibers with an average fiber diameter of 30 nm were observed (Figure 7 (j1)), indicating that chloroform can defibrate the hydrophobic nanofiber aggregate 10. By immersing the hydrophobic nanofiber aggregate 10 in dichloromethane, a nanofiber structure with an average fiber diameter of 20 nm was obtained, suggesting that it can be defibrated by immersion in dichloromethane (Figure 7(j2)). When the hydrophobic nanofiber aggregate 10 was immersed in DMF, a network of nanofibers with an average fiber diameter of 50 nm was observed (Figure 7 (j3)), suggesting that it could be defibrated by immersion in DMF.
[0091] When the hydrophobic nanofiber aggregate 11 was immersed in dichloromethane, a fibrous arranged structure with an average fiber diameter of 20 nm was observed (Figure 7 (k2)), indicating that dichloromethane is capable of defibrating the hydrophobic nanofiber aggregate 11 into nanofibers.
[0092] For the hydrophobic nanofiber aggregate 12, no nanofiber structure was obtained when it was immersed in any of chloroform, dichloromethane, and DMF. The dispersions immersed in chloroform and dichloromethane formed a porous surface (Figure 8 (l1, l2)). The dispersion immersed in DMF produced particles with a diameter of 100 nm, which were not arranged in a stripe-like pattern (Figure 8 (l3, l4)). Thus, SPM observation did not confirm that the hydrophobic nanofiber aggregate 12 could be defibrated into nanofibers when immersed in any of the solvents. However, as described below, it was suggested that it could be defibrated into hydrophobic nanofibers by immersing in DMSO.
[0093] (Scanning Electron Microscope (SEM) Observation-2) 9(a)-(l) show SEM images of the freeze-dried products obtained by immersing hydrophobic nanofiber assemblies 1-12 in DMSO. The freeze-dried products were used as the observation subjects here because they were expected to highly reflect the dispersion state in the solution.
[0094] Hydrophobic nanofiber assemblies 1-5 were highly swellable in DMSO, and the freeze-dried samples after immersion contained mainly sheet-like and amorphous structures (Figures 9(a)-(e)). However, considering the high dispersibility of these product solids in DMSO, the hygroscopicity of DMSO, and the ice crystal-mediated aggregation properties of polysaccharide nanofibers during the freeze-drying process, these non-fibrous structures are likely formed by the reconstruction of highly solvated and defibrated nanofibers. Thus, these SEM images suggest that the solid hydrophobic nanofiber assemblies 1-5 were defibrated by immersion in DMSO. Thus, it is suggested that immersion in DMSO can defibrate the hydrophobic nanofiber assemblies 1-5.
[0095] As shown in Figures 9(f) to (l), the SEM photographs of the products from hydrophobic nanofiber aggregates 6 to 12 show that the freeze-dried samples contain a large number of nanofibers with an average fiber diameter of 100 nm or less, suggesting that hydrophobic nanofiber aggregates 6 to 12 are defibrated by immersion in DMSO.
Claims
1. At least one hydrogen atom of a hydroxy group in at least one glucose unit is -COR 1 (R 1 A hydrophobic nanofiber comprising a β-1,3-glucan substituted with a β-1,3-hydroxybutyric acid group (representing an aliphatic or aromatic hydrocarbon group).
2. The β-1,3-glucan has the following formula (I): (In formula (I), R 2 each independently represents a hydrogen atom or -COR 1 represents R 1 represents an aliphatic or aromatic hydrocarbon group, and n represents an integer of 1 or more. 2 At least one of the following is -COR 1 (It is) The hydrophobic nanofiber of claim 1 having a structure represented by:
3. The β-1,3-glucan has the following formula (II): (In formula (II), R 2 each independently represents a hydrogen atom or -COR 1 represents R 1 represents an aliphatic or aromatic hydrocarbon group, and m represents an integer of 1 or more. 2 At least one of the following is -COR 1 (It is) The hydrophobic nanofiber according to claim 1 or 2, having a structure represented by:
4. -COR 1 R in 1 The hydrophobic nanofiber according to any one of claims 1 to 3, wherein is an aliphatic hydrocarbon group, and the aliphatic hydrocarbon group is a linear or branched aliphatic hydrocarbon group having 1 to 25 carbon atoms.
5. -COR per glucose unit of β-1,3-glucan 1 The hydrophobic nanofiber according to any one of claims 1 to 4, wherein the number is 1.00 or greater.
6. -COR per glucose unit of β-1,3-glucan 1 The hydrophobic nanofiber of claim 1 , wherein the number is 2.90 or less.
7. The hydrophobic nanofiber according to claim 1 , used as a fibrous filler.
8. An assembly of hydrophobic nanofibers according to any one of claims 1 to 7.
9. A method for producing a hydrophobic nanofiber according to any one of claims 1 to 7, At least one hydrogen atom of a hydroxy group in at least one glucose unit is -COR 1 (R 1 The method includes immersing an aggregate of hydrophobic nanofibers comprising β-1,3-glucan substituted with a β-1,3-glucan substituted with a hydroxy group (wherein m represents an aliphatic or aromatic hydrocarbon group) in an organic solvent to obtain hydrophobic nanofibers.
10. The method according to claim 9, wherein the organic solvent comprises one or more selected from the group consisting of halogenated solvents, protic solvents, and aprotic solvents.
11. -COR per glucose unit of β-1,3-glucan 1 The method according to claim 9 or 10, wherein the number is 1.00 or more.
12. -COR per glucose unit of β-1,3-glucan 1 The method according to any one of claims 9 to 11, wherein the number is 2.90 or less.
Citation Information
Patent Citations
Porous film
JP2012092223A
??-1,3-glucan nanofiber and its manufacturing method
JP2014037657A
Injection molding method, injection-molded article and resin composition therefor
JP2015086254A
Overcoat precursor liquid, overcoat formation method and composite
JP2017101177A
Paramylum derivative, manufacturing method therefor, nanofiber and manufacturing method therefor
JP2017179182A